Efficacy of different preoperative antiseptics in preventing a risk of surgical site infections: a systematic review and meta‑analysis of randomized controlled trials - Lutao Yang; Shunxin Liao; Qing Cao; Sanjay Rastogi (Videosurgery and Other Miniinvasive Techniques)
Introduction: Surgical site infection (SSI) is a predominant postoperative complication that markedly increases health care expenses. Published systematic reviews, meta-analyses and international guidelines vary in their recommendations for the most effective preoperative skin antiseptic solutions and their concentrations.